تحليل الأخطاء في نطق الحروف الهجائية عند ضوء نظرية الإمام خليل بن أحمد لدى تلاميذ مدرسة الحكمة الدينية مالانج - Aulia, Herlina (Maharaat Lughawiyyat: Jurnal Pendidikan Bahasa Arab, 2023)
This study explains about the mispronunciation of hijaiyyah letters by using the theory of Imam Kholil bin Ahmad as the basis. Based on the results of observation, it is found that the students of Madrasah Diniyah Al-Hikmah mispronounced the hijaiyyah letters and were not able to pronounce the hijaiyyah letters fluently and correctly in accordance with the makhorijul of the letters and the properties of the letters. This study aims to describe the forms of the hijaiyyah letters mispronunciation, the reasons affecting the mispronunciation of hijaiyyah letters, and the efforts made by teachers to correct the mispronunciation of hijaiyyah letters. This study uses a descriptive qualitative method. The data collection techniques used are observation, interviews, documentation, and tests. The data analysis consists of three stages, including data reduction, data presentation, and conclusion drawing. For testing the validity of the data, a triangulation study is used. The results of this study are the mispronunciation of hijaiyyah letters is divided into four forms; those are letter replacement, letter deletion, letter addition, and letter disguise. في هذا البحث بيّنت الباحثة عن تحليل الأخطأ في نطق الحروف الهجائية عند ضوء نظرية الإمام خليل بن أحمد. ومن عملية الملاحظة وجدت الباحثة أنّ كثير من التلاميذ المدرسة الدينية الحكمة يخطؤون في نطق الحروف الهجائية ولم يستطيعوا أن ينطقوا الحروف الهجائية فصيحة وواضحة بناء على مخارج الحروف وصفات الحروف. استخدمت الباحثة المدخل الكيفي الوصفي. وأمّا طريقة جمع البيانات هي الملاحظة والمقابلة والوثائق والاختبار. وكان تحليل البيانات في هذا البحث الكيفي تتكون من ثلاثة طرق لحصول بيانات البحث وهي تقليل البيانات وتقديم البيانات والاستخلاص. واستخدمت الباحثة طريقة تأكيد صحة البيانات بطريقة التثليث. نتائج هذا البحث هي أنّ أشكال الأخطأ في نطق الحروف الهجائية هناك أربعة أشكال، وهي إبدال الحروف وحذف الحروف وزيادة الحروف وتشوية الحروف.